Gender Equality in Islam: The Implementation of Adat Sanctions for Adultery Among the Malay Tribe in West Kalimantan - Khaliq, Muhammad Nur; Arif, Mahmud; Parwanto, Wendi; Rahman, Ali; Rizki, Meisya Anggraini (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study aims to examine the gender dynamics in the implementation of basadosa sanctions for adultery cases in Sintang Regency, West Kalimantan. The study uses a qualitative research methodology. A descriptive-analytical approach will be applied to explore how these sanctions are implemented on male and female offenders, with a focus on gender differences and their impacts. This research will analyze the distinctions in the application of basadosa sanctions and the social, psychological, and economic consequences experienced by male and female offenders. The findings of this study regarding the application of basadosa sanctions in adultery cases in Sintang Regency, West Kalimantan, reveal significant gender inequality, with women often receiving harsher social sanctions compared to men. Social ostracism and humiliation are more frequently experienced by women, leading to more severe psychological and social impacts for them. This occurs due to social norms that view women as the guardians of family honor, while men are more often given leniency or forgiveness. The implications of this research provide critical insights into the influence of basadosa sanctions in reinforcing or challenging gender inequality, as well as providing policy recommendations to promote gender equality in the application of customary law.